Rhizofiltration Process To Remove Organic And Heavy Metals In KotaSAS Lake - Nur Hanisah, Shamsudin (2023)
Polluted water because of the pollutant process, also known as essential negative impacts by cyanobacterial species resistance to the growth of biomass in a freshwater biological system. In-situ treatment of high-level contaminated soils with phytoremediation is a viable option. Phytoremediation is a plant-mediated technique that entails using plants to absorb and eliminate elemental contaminants, or to reduce their concentration or bioavailability in the soil. Plants could take substances from the soil through their root system, even at low concentrations. Phytostabilization, phytoextraction, phytovolatilization, and phytofiltration are the most often employed phytoremediation techniques in organic and heavy metal-polluted soil and water remediation. The objectives of this research were to enhance water quality and reduce pollution levels in the KotaSAS Lake by decomposing, absorbing, and metabolizing it using living green plants to recover water and soil resources in-situ. The tests and studies will take place in the field for in-situ data and in the University Malaysia Pahang Environmental Laboratory and Central Laboratory for ex-situ data collection. The wastewater was collected at KotaSAS Lake area, and it was analyzed to collect the water quality data. The lake water was collected and poured into few different containers. It has 2 type of plant that has been used which is Lepironia Articulata and Typha Angustifolia. All containers used the different type of plants. A total of 10 parameters listed below: Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Total Suspended Solid (TSS), pH, Temperature, Turbidity, Iron (Fe), Manganese (Mn), Nitrate (NO3) and Aluminium (Al) as for water quality evaluation. Finally, there are considerable differences between the plants before and after treatment.